Serum 25-Hydroxyvitamin D Concentration Status and Neonatal Immune Function: New Perspectives in Anticipating Late Onset Sepsis among Preterm Neonates at Tertiary Care Centres (A Prospective Study) - Mohammed Elbehery, Mohammed Younis; Abdelfattah Abdellatif, Naguib Abdellatif; Mohamed Ahmed, Mohamed Abdelsalam; Hashem Abdelgaeid, Hashem Abdelsabor; Abdelaziz, Khaled Mosbah; Ali Elagamy, Ali Elsayed; Abdelnaby Ghallab, Mahmoud Mohamed; Mahmoud, Mohamed Saber; Elfattah M. Hassan, Ismail Abd; Abdelsamie Fadl, Ahmed Abdelsamie; Abdelgawad Nasr, Asmaa Elsaudi; Mohammed Abo El Ela, Eman El Sayed; et al. (International Journal of Child Health and Nutrition, 2025)
Objective: This study aims to investigate the impact of low vitamin D levels in cord blood on the incidence of neonatal sepsis in preterm infants. Patients and Methods: This prospective study was conducted at Al-Azhar and Helwan University Hospitals from September 2024 to January 2025. 150 neonate premature infants with a gestational age of <37 weeks were enrolled. In the present study, vitamin D deficiency (group 1, n=75) was defined as a 25-hydroxyvitamin D (25(OH)D) concentration <15 ng/mL; and vitamin D sufficiency (group 2, n =75), 25(OH)D concentration ≥15 ng/mL. Results: All markers were higher in Group 1 compared to the other groups (P < 0.05). Interestingly, the mean Del PCT was lower in group 2 compared to different groups. The cut-off of the umbilical cord CRP was 10.5 mg/L, the sensitivity, specificity, PPV and NPV were 41, 88.0, 29 and 28%, respectively. At a PCT cut-off of 1.18 ng/mL, the sensitivity, specificity, PPV and NPV were 79, 91, 51 and 61%, respectively Conclusion: Our study is one of the few that examines the relationship between neonatal sepsis in preterm newborns and the level of vitamin D in cord blood. Based on the findings of our investigation, we concluded that neonatal sepsis in preterm newborns is not related to vitamin D levels in the cord blood. To investigate these findings further, a larger patient sample or randomized controlled trials are required.